The Influence of Plate Geometry on the Cyclic Bearing Behavior of Single Helical Piles in Silty Sand - Faxiang Gong; Wenni Deng; Xueliang Zhao; Xiaolong Wang; Kanmin Shen (Journal of Marine Science and Engineering, 2025)
Helical piles are widely used in geotechnical engineering, and their rapid installation and service reliability have attracted significant interest from the offshore wind industry. These piles are frequently subjected to cyclic loading in complex marine environments. Although the cyclic bearing behavior of helical piles has been studied, most research has focused on soil properties and loading conditions, with a limited systematic analysis of plate parameters. Moreover, the selection of plate parameters is not explicitly defined. As a crucial preliminary step in the capacity calculation, it is vital for the design of helical piles. To address this gap, the present study combines physical modeling tests and finite element simulations to systematically evaluate the influence of plate parameters on their cyclic bearing behavior. The parameters investigated include the plate depth, the plate diameter, plate spacing, and the number of plates. The results indicate that, under the same embedment conditions, cumulative displacement increases with the plate depth, with a critical embedment depth ratio of Hcr/D = 6 under cyclic loading conditions, but decreases with the number of plates. Axial stiffness increases with the plate depth, diameter, and number of plates, with an increase ranging from 0.5 to 3.0. However, the normalized axial stiffness decreases with these parameters, reaching a minimum value of 1.63. The plate spacing has a minimal influence on cyclic bearing behavior. Additionally, this study examines the evolution of displacement and stiffness parameters over repeated cycles in numerical simulations, as well as the post-cyclic pullout capacity of the helical pile foundation, which varies between −5% and +12%.